Mechanical Extraction of a Massive Intracoronary Thrombus from the Super-Dominant Right Coronary Artery in Thrombogenic Lung Cancer Patient - Kim, Dong-Kie (Korean Circ J, 2015)
The congenital absence of the left circumflex artery and a compensatory super-dominant right coronary artery (RCA) is a very rare benign coronary anomaly in the clinic. The presence of a massive thrombus in the super-dominant RCA can lead to fatal results in cases of acute myocardial infarction, unless the thrombus is mechanically removed. Aspiration of the thrombus using a 6 Fr right Judkins guide catheter is useful to extract a massive thrombus and is both safe and effective. We report a case of complete revascularization of the super-dominant RCA after thrombus aspiration using a 6 Fr Judkins right catheter in a patient with acute inferior and inferolateral wall myocardial infarction.